Negotiating autobiographical truth: Embodying sensation in the narrative screenplay. (1st March 2020) - Wilson, Gavin
This article examines how screenwriting adaptations of written material speak of levels of truth-telling within various autobiographical texts. These include literary adaptations by Marguerite Duras: Hiroshima Mon Amour (1959) and The North China Lover (1992), and the autobiographical filmmaking of Maya Deren: Meshes of the Afternoon (1946) and The Very Eye of Night (1958). I argue that descriptions of tactile sensation necessarily remain codified in screenplays, their connotations left hanging even when the filmmaking process often falls short of depicting final truth. What remains is an unresolved problematic perception standing in for an experience. Our own experience of cinema can invariably be one wherein neither words nor images appear, or reappear, as to how they felt for the screenwriter. Is this a wholly negative situation, or merely the continuation of mediation, remediation and the contingent transposition of one medium into another? Drawing on examples from the screenwriting and/or filmmaking of Duras and Deren, I discuss why the screenwriter always writes in personal terms (because the personal is inescapable), and that this is a personal experience of imagination through the writing. Moreover, I test the idea that screenwriting only emerges in a form that we can recognize as truth, through its depictions of tactility and its representations of sensation.